EVALUATION OF KNOWLEDGE AND AWARENESS ON AUTOIMMUNE MULTIPLE SCLEROSIS AMONG PHARMACY AND NURSING STUDENTS OF CHITRADURGA – A DESCRIPTIVE CROSS-SECTIONAL STUDY - Zakir A, Mohammed; LALREMSANGI; Siddiq, Abubaker (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The study’s goals were to evaluate knowledge and awareness among the students regarding multiple sclerosis (MS) and to compare the knowledge of the same among pharmacy and nursing students. Methods: This is a descriptive cross-sectional study conducted among the pharmacy and nursing students of Chitradurga, carried out for 6 months. The questionnaire was distributed among students containing 15 questions regarding MS. Each accurate response received a score of “1,” while every incorrect response received “0.” The frequency and percentage were obtained using descriptive approaches. The data are presented as a frequency distribution of mean and standard deviation (SD). Results: A total of 500 participants were enrolled in the study, among which 319 were pharmacy students and 181 were nursing students. The results analyzed that the knowledge assessment mean scores of pharmacy students were higher than those of nursing students. It also showed that students who come under the age group of 23–27 years have higher knowledge compared to the 18–22-year age group. Conclusion: This study concluded that pharmacy students had a piece of better knowledge than nursing students since these occupations play such a significant part in providing health care, knowledge, and understanding need to be raised. Hence, awareness and education about MS should be conducted to enhance students’ knowledge.